Dose–response between frequency of interruption of sedentary time and fasting glucose, the dawn phenomenon and night‐time glucose in Type 2 diabetes. Issue 3 (12th October 2018) - Paing, A. C.; McMillan, K. A.; Kirk, A. F.; Collier, A.; Hewitt, A.; Chastin, S. F. M.
Abstract: Aim: To explore the dose–response between frequency of interruption of sedentary time and basal glucose (fasting glucose, the dawn phenomenon and night‐time glucose) in Type 2 diabetes. Methods: In a randomized three‐treatment, two‐period balanced incomplete block trial, 12 people with Type 2 diabetes (age, 60.0 ± 3.2 years; BMI, 30.2 ± 1.4 kg/m 2 ) completed two of three conditions: sitting for 7 h interrupted every 60 min (Condition 1), 30 min (Condition 2), and 15 min (Condition 3) by 3‐min light‐intensity walking breaks. The activPAL3 and FreeStyle Libre were used to assess physical activity/sedentary behaviour and continuous glucose profile. Standardized meals were provided, and changes in basal glucose of the nights and early mornings before and after treatment conditions were calculated (mean ± SE). Results: After treatment conditions, fasting glucose and duration of the dawn phenomenon were lower for Condition 3 (−1.0 ± 0.2 mmol/l, P < 0.02; −3.1 ± 1.3 h, P = 0.004) compared with Condition 1 (−0.1 ± 0.2 mmol/l; 1.9 ± 1.2 h). The magnitude of the dawn phenomenon was reduced in Condition 3 (−0.6 ± 0.4 mmol/l, P = 0.041) compared with Condition 2 (0.6 ± 0.3 mmol/l). Night‐time glycaemic variability (coefficient of variation) was reduced in Condition 3 (−9.7 ± 3.9%) relative to Condition 2 (6.1 ± 4.8%, P < 0.03) and Condition 1 (2.5 ± 1.8%, P = 0.02). There was no change in night‐time mean glucose. Conclusions: Frequent interruptions of prolonged sitting with 3 min of light‐intensity walking breaks every 15 min improves fasting glucose, the dawn phenomenon and night‐time glycaemic variability, and this might be a simple therapeutic intervention to improve glucose control. Clinicaltrials.gov Identifier: NCT02738996 What's new?: There is a dose–response between how often sitting is interrupted and basal glucose control. Frequent interruptions of prolonged sitting with short light‐intensity walking breaks every 15 min reduce fasting glucose, magnitude of the dawn phenomenon, duration of the dawn phenomenon and night‐time glycaemic variability. Interrupting sedentary time every 15 min with short light‐intensity walking breaks could be a simple therapy to improve basal glucose control.